Integrative training projects in vocational training - Rosales Moisés, Huerta (2021)
The development of integrative projects in professional training aims to integrate formative research with social responsibility actions, to contribute to the improvement of the quality of professional training, in which research as a process of exploration and discovery of new knowledge, contributes to the technological development that generates technologies, processes or products, resulting in technological innovation, which allows the transfer of technology for its use for the benefit of society. This report uses an action research methodology aimed at verifying in practice the solution of the problem of learning to investigate from intervening in the solution of the problems of the context. The result reflects that students enhance their investigative abilities by improving their observation, detection, analysis and use of information to translate it into scientific communications and better still, if they respond to seeking the solution of problems in the context. In conclusion, the application of integrative training projects enhances the ability to investigate from reality and contribute to the training of the human being researcher with human, social and environmental responsibility.